Growth Performance and Intestinal Health of Broiler Chickens Supplemented with Coriander Oil Nanoemulsion in Drinking Water - K. Sholiha; N. D. Dono; B. Ariyadi; Zuprizal (Tropical Animal Science Journal, 2023)
This research was conducted to investigate the effects of coriander (Coriandrum sativum) essential oil nano emulsion (NCSEO) in drinking water on growth performance and intestinal health (intestinal microbiota and histomorphology) of broiler chickens. A total of 180 one-day-old male broiler chickens were randomly allocated into five treatments with four replicates and 9 chicks per replicate pen. Birds were provided NCSEO via drinking water. The treatments applied were as follows: without any addition (T0), drinking water added with 50 ppm antibiotic tetracycline (T1), drinking water added NCSEO at 25 μL/L (T2), 50 μL/L (T3), and at 100 μL/L (T4). Variables observed were characteristics of NCSEO, growth performance, intestinal microbiota (LAB and Salmonella spp.), and histomorphology of intestine (villus height, villus width, crypt depth, villus height to crypt depth ratio). All collected data were analyzed using ANOVA in a completely randomized design. Results showed that the particle size of NCSEO was 13.1 nm with PDI 0,257, zeta potential -5.65 mV, stable, and spherical shape. The addition of NCSEO improved (p<0.05) final body weight, weight gain, and FCR, while no significant differences in feed intake and water intake, increased the LAB population (p<0.05) whereas Salmonella spp. was not found, and stimulated (p<0.05) villus height and width. The addition of NCSEO at 50 μL/L resulting the highest promoting effect on growth performance, intestinal microbiota, and intestinal histomorphology of broiler chickens. It can be concluded that 50 μL/L of NCSEO as an alternative to antibiotics can be supplemented in drinking water to improve the growth performance and intestinal health of broiler chickens.